Impacts of Taking, Trade and Consumption of Terrestrial Migratory Species for Wild Meat - Coad, L.M.; Willis, J.; Maisels, F.; Funk, S.M.; Doughty, H.; Fa, J.E.; Gomez, J.; Ingram, D.J.; Li, Y.; Nihotte, L.; Paemelaere, E.A.D.; Sartoretto, E.; et al. (Convention on Migratory Species, 2021)
This report – the first of its kind – identifies the impacts of wild meat taking, trade and consumption of terrestrial species that are protected by CMS. It puts a spotlight on species such as antelopes, primates, and carnivores and points to the need for greater attention to the taking of globally protected wildlife purely for domestic use as opposed to international trade. The study also highlights the need to assess national legislation and enforcement capacity, as well as the linkages between zoonotic diseases and wild meat.